2008
DOI: 10.1093/epirev/mxn009
|View full text |Cite
|
Sign up to set email alerts
|

Blues from the Neighborhood? Neighborhood Characteristics and Depression

Abstract: Unipolar major depression ranks among the leading contributors to the global burden of disease. Although established risk factors for depression include a variety of individual-level characteristics, neighborhood etiologic factors have been relatively understudied, with several such attributes (neighborhood socioeconomic status, physical conditions, services/amenities, social capital, social disorder) possessing plausible linkages to depression. Using the PubMed database (1966-2008) and the Social Sciences Cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
305
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(322 citation statements)
references
References 53 publications
11
305
2
4
Order By: Relevance
“…However, the few studies that analyzed the incidence of depression depending on the place of residence have demonstrated ambiguous results. Peen et al found that psychosomatic disorders, including depression, occurred more frequently in city patients; other researchers found a higher incidence of depression among residents of rural areas than the urban areas [4,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the few studies that analyzed the incidence of depression depending on the place of residence have demonstrated ambiguous results. Peen et al found that psychosomatic disorders, including depression, occurred more frequently in city patients; other researchers found a higher incidence of depression among residents of rural areas than the urban areas [4,10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that by 2020, depression will be among the three main health problems worldwide [4]. In many studies, depression has appeared to be an independent predictor of cardiovascular diseases, including coronary heart disease, to facilitate body weight gain and increase the percentage of patients with overweight or obesity, especially abdominal obesity and accumulation of metabolically active visceral adipose tissue (VAT) [2,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an increased drift towards 1 disadvantaged urban environments of people who have suffered a decline in mental health and 2 perhaps an associated slide in social standing (Lapouse et al, 1956), or an outmigration of the more 3 wealthy and healthy from larger conurbations to suburban areas (O'Reilly et al, 2001). No study to 4 date has analysed all three hypotheses concurrently and, of late, studies have begun suggesting 5 other factors which may be affecting health in urban areas including pollution, air traffic noise, social 6 networks and the quality of the built environment (Galea et al, 2005;Kim, 2008). 7 8 This aim of this paper is to determine if (i) urban residence is associated with an increased risk of 9 suffering from common mood disorders such as anxiety and depression (as measured by uptake of 10 anxiolytic and antidepressant medication), and (ii) to determine if this association is independent of 11 psychosocial stressors, area disadvantage and selective migration.…”
Section: Introductionmentioning
confidence: 99%
“…Moving beyond an individual-based approach to health to one focused on settings where people live, work and play, researchers are attempting to identify neighbourhood characteristics as intervention targets for reducing health inequalities. Exposure to neighbourhood physical and social environments has been linked to health behaviours such as smoking (Frohlich et al, 2002, Chow et al, 2009, Ellaway and Macintyre, 2009, diet (Chow et al, 2009) and physical activity (Chow et al, 2009), and health outcomes including self-rated health (Pickett andPearl, 2001, Riva et al, 2007), cardio-vascular diseases (Riva et al, 2007, Chaix, 2009, Chow et al, 2009, obesity (French et al, 2001) and mental health (Egan et al, 2008, Cohen et al, 2003, Kim, 2008). …”
Section: Introductionmentioning
confidence: 99%